Experimental characterization of a household heat pump tumble dryer noise. (January 2022) - Čurović, Luka; Novaković, Tadej; Gatarić, Pero; Murovec, Jure; Prezelj, Jurij
Abstract: In this paper, an experimental approach for acoustic characterization of a household heat pump tumble dryer is developed. The main noise sources including BLDC motor, centrifugal fan, drain pump, and ventilation duct were identified using an acoustic camera survey based on beamforming, sound pressure level, directivity, and laser Doppler vibrometer vibration velocity measurements. In addition, noise reduction measures were taken, and sound power level and directivity measurements were used to evaluate the significance of the identified sources on the total noise emission. As a result, the A-weighted sound power level was reduced from 64.8 to 60.4 dB and the directivity pattern was improved. The proposed experimental approach for noise identification and the validation approach can be applied to other complex household appliances of similar size.